Can Households Predict where the Macroeconomy is Headed? - Kamil Kladivko; Pär Österholm (Örebro University School of Business, 2020)
In this paper, we evaluate households' directional forecasts of inflation and the unemployment rate in Sweden. The analysis is conducted using monthly forecasts from the National Institute of Economic Research's Economic Tendency Survey that range from January 1996 until August 2019. Results indicate that households have statistically significant ability to forecast where the unem-ployment is headed, but they fail in predicting the direction of future inflation.
Keywords: E37; 330; Survey data; Directional forecasts; Inflation; Unemployment